Perinatal death from listeriosis - Galup-Leyva, Mariajosé (2021)
A 35-year-old woman, with 22 weeks of gestation, presented fever without a determined origin and decreased fetal movements, evolving with fetal death due to Listeria monocytogenes infection, evidenced by blood cultures and the pathological study of the fetus and placenta.